Evaluasi Penyimpanan Obat di Gudang Farmasi Puskesmas Mangunsari Kota Salatiga: Evaluation of Drug Storage at the Pharmacy Warehouse of the Mangunsari Health Center, Salatiga City - Dewi, Vionica Citra; Yuswantina, Richa (Journal of Holistics and Health Sciences, 2022)
Drug storage is a pharmaceutical job in which the activities of regulating pharmaceutical supplies according to predetermined requirements are accompanied by an information system that always guarantees the availability of pharmaceutical supplies. The purpose of this study was to get an overview of drug storage and to know the evaluation of drug storage in the pharmacy warehouse of the Mangunsari Health Center in Salatiga city based on the Minister of Health Regulation No. 74 of 2016. The research design used a descriptive method with observations of the research object and direct interviews. Collecting data by filling out the check list sheet indicators based on the results of observations and interviews. The data is presented in the form of a check list table and then analyzed by comparing the drug storage indicators with the actual situation. The results of this study show that the percentage of storage parameters for warehouse requirements is 92.8%, the percentage of drug storage parameters is 100%, and the percentage of storage parameters for the stok card recording system is 100%. Based on the results of the research on evaluation of drug storage in the warehouse of the Mangunsari Health Center, Salatiga City, it is in accordance with Minister of Health Regulation No. 74 of 2016 on drug storage parameters and stok card recording systems. ABSTRAK Penyimpanan obat merupakan pekerjaan kefarmasian dimana kegiatan pengaturan pembekalan farmasi menurut persyaratan yang telah ditetapkan disertai dengan sistem informasi yang selalu menjamin ketersediaan perbekalan farmasi. Tujuan pada penelitian ini untuk mendapatkan gambaran penyimpanan obat dan mengetahui evaluasi penyimpanan obat di gudang farmasi Puskesmas. Desain penelitian menggunakan metode deskriptif dengan pengamatan terhadap objek penelitian dan wawancara langsung. Pengumpulan data dengan cara mengisi indikator lembar chek list berdasarkan hasil pengamatan dan wawancara. Data disajikan dalam bentuk tabel chek list kemudian dianalisa dengan cara membandingkan indikator penyimpanan obat dengan keadaan sebenarnya. Hasil penelitian ini menunjukkan gambaran bahwa persentase parameter penyimpanan persyaratan gudang 92,8% persentase parameter penyimpanan obat 100%, dan persentase parameter penyimpanan sistem pencatatan kartu stok 100% Berdasarkan hasil penelitian evaluasi penyimpanan obat di gudang Puskesmas Mangunsari Kota Salatiga sudah sesuai dengan Permenkes No 74 Tahun 2016 pada parameter penyimpanan obat dan sistem pencatatan kartu stok.